Increased Circulating T Follicular Helper Cells Are Inhibited by Rituximab in Neuromyelitis Optica Spectrum Disorder - Zhao, Cong; Li, Hong-Zeng; Zhao, Dai-Di; Ma, Chao; Wu, Fang; Bai, Ya-Nan; Zhang, Min; Li, Zhu-Yi; Guo, Jun (Frontiers in Neurology, 2017)
Neuromyelitis optica spectrum disorder (NMOSD) is a severe autoimmune disease of the central nervous system (CNS). The existence of autoantibody targeting aquarporin-4 (AQP4-Ab) indicates the involvement of humoral immunity in the pathogenesis of this disease. Rituximab (RTX), a monoclonal antibody against CD20, has been used to treat NMOSD by depleting circulating B cells and overall satisfactory outcome has been achieved. Although T follicular helper (Tfh) cells have been proved to regulate B cell activation and antibody production, the role of these cells in MNOSD as well as the impact of RTX treatment on these cells remain less understood. In this study, we found that frequencies of circulating Tfh cells (cTfh) and B cells together with the related cytokines, IL-21 and IL-6, were closely correlated with disease activity of NMOSD. Furthermore, B cell depletion with RTX treatment inhibited the expansion of cTfh cells; and these effects were achieved through eliminating IL-6-producing B cells and blocking the direct contact between cTfh cells and B cells. These findings imply the complicated crosstalk between cTfh cells and B cells and may provide a novel therapeutic target for NMOSD.